2004
DOI: 10.1111/j.1813-6982.2004.tb00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Mega‐sporting Events in Developing Nations: Playing the Way to Prosperity?

Abstract: ABSTRACT:Supporters of mega-sporting events such as the World Cup and Olympics claim that these events attract hoards of wealthy visitors and lead to lasting economic benefits for the host regions. For this reason, cities and countries compete vigorously for the right to stage these spectacles. Recently, developing countries have become increasingly vocal in demanding that they get the right to share in the economic benefits of these international games. China, for example, has been awarded the 2008Summer Olym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 4 publications
1
74
0
7
Order By: Relevance
“…The Montreal Olympics had highly problematic long-term economic outcomes for the city. An analysis of the more recent 1994 World Cup in the United States of America revealed that opposed to the expected $4 billion gain, host cities experienced losses ranging between $5.5-$9.3 billion Matheson and Baade 2004). Non-host cities can also experience reductions in their revenue which may be long-lasting.…”
Section: Development Impacts Of Mega-events: Reflections From the Intmentioning
confidence: 99%
See 4 more Smart Citations
“…The Montreal Olympics had highly problematic long-term economic outcomes for the city. An analysis of the more recent 1994 World Cup in the United States of America revealed that opposed to the expected $4 billion gain, host cities experienced losses ranging between $5.5-$9.3 billion Matheson and Baade 2004). Non-host cities can also experience reductions in their revenue which may be long-lasting.…”
Section: Development Impacts Of Mega-events: Reflections From the Intmentioning
confidence: 99%
“…In addition to these experiences, as Matheson and Baade (2004) suggest, displacement of public funds is a key area of complaint. Public spending on projects and maintenance often means that budget cuts are made in other areasa problem which becomes exacerbated if costs escalate.…”
Section: Development Impacts Of Mega-events: Reflections From the Intmentioning
confidence: 99%
See 3 more Smart Citations